ANALISIS SIFAT ORGANOLEPTIK SAMBAL “LU’AT” KHAS PULAU TIMOR - Hyldegardis Naisali; Deseriana Bria (Yayasan Nusantara Hasana Berdikari, 2022)
Sambal lu'at is a special chili sauce for the people of Timor Island and is a chili sauce that is prepared traditionally. This chili sauce is usually served as a complementary food for big events or for household consumption. The materials used varied, so the researchers in this study added lime and a combination of treatments to get good quality and be acceptable to consumers. The method used in this study was a 2-factor Completely Randomized Design (CRD), factor I salt concentration (G), G1 = 5%, G2 = 10% and factor 2 fermentation time (F), F1 = 0 days, F2 =3 days, F3=7 days. Furthermore, organoleptic tests were carried out to obtain the best treatment using attributes (color, aroma, taste and texture). The main objective of the study in this article is to determine the panelist's level of preference on a hedonic scale of 1-5 (dislike-very like) with sensory attributes of color, aroma, taste and texture. The results showed that the salt concentration of 5% and the fermentation time of 0 days had the highest value, namely 4.53 (likes).